EXTERNAL IMPACT OF CONCRETE MATTRESS ON CARBON STEEL PIPE - BIN SHAIFUL BAHRIN , SYAQIF HAZIM (Universiti Teknologi PETRONAS, 2018)

(untitled)
This research investigates the external impact of concrete mattress on a carbon steel pipeline. Three different orientation are tested on three pipe size which are 10, 16, and 20 inches each having different wall thickness values. Orientation 1 is referred to as a single concrete block per row is resting on top of the pipeline. Orientation 2 on the other hand, is when two concrete block per row are resting on top of the pipeline, while Orientation 3 is having the same two concrete blocks per row resting on top of the pipeline but the faces are touching each other. The pipeline condition which was tested is in intact condition. Modelling work were done by Solid Work while simulation work using ANSYS. The simulation involved pipe condition located at 70 m underwater under the normal operating condition. Deformation and stresses within the pipe were observed. Results showed that the pipeline were not significantly affected by deformation and stresses.